Transitioning to regenerative urbanism - Thomson, Giles Redding (Curtin University, 2016)
This thesis describes a framework for transitioning to regenerative urbanism. Regenerative urbanism represents a new planning paradigm that optimises urban fabric and applies a regenerative design overlay to deliver highly liveable and sustainable urban development. This approach integrates across systems (energy, transport, water, waste, food, biodiversity), and scales (plot, precinct, city). Mainstreaming regenerative urbanism could usher in a period of planetary biosphere regeneration by facilitating a global network of net positive impact regenerative cities.